2004
DOI: 10.1097/01.coc.0000047127.46594.c0
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Arising in a Second Branchial Cleft Cyst

Abstract: The existence of primary branchiogenic carcinoma is controversial. In 1950, Martin et al. established four criteria for the diagnosis of primary branchiogenic carcinoma. In 1989, Khafif et al. proposed new criteria, which are currently most recognized in the literature. A pathologic description of the surgical specimen is analyzed and compared with a critical review of the literature. A case is presented in which imaging established the diagnosis of a benign second branchial cleft cyst 2 years prior to the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 11 publications
0
23
0
1
Order By: Relevance
“…Reports indicate a significant incidence of local recurrence, frequent node metastases, and occasionally death due to disease. [33][34][35] The most recent reviews of the subject were those published by Hong and colleagues 35 in 1999 and by Girvigian and colleagues 36 …”
Section: Branchial Cleft Cysts Sinuses and Fistulasmentioning
confidence: 99%
“…Reports indicate a significant incidence of local recurrence, frequent node metastases, and occasionally death due to disease. [33][34][35] The most recent reviews of the subject were those published by Hong and colleagues 35 in 1999 and by Girvigian and colleagues 36 …”
Section: Branchial Cleft Cysts Sinuses and Fistulasmentioning
confidence: 99%
“…Due to their shared anatomic region, primary branchial cleft cyst carcinoma needs to be distinguished from cystic cervical metastases arising from occult primary tumors in the upper aerodigestive tract, which have a much higher incidence rate (1,2,5,7,8). The majority of cystic cervical metastases originate from Waldeyer's ring, including the nasopharynx, tonsil and the base of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that most of the so-called primary branchial cleft cyst carcinomas are actually cystic cervical metastases resulting from oropharyngeal carcinoma, most commonly originating in the tonsils in the upper aerodigestive tract (5). To date, there are only approximately 40 cases of primary branchiogenic carcinoma reported in the literature, which were found mostly in men aged 40-60 with the majority of cases involving second branchial cleft cysts (6,7). In terms of primary carcinoma in the first branchial vestigium, to the best of our knowledge, there are only 5 reported cases, all of which occurred in adults (1,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the histology illustrat ing a transition of the epithelium to the carcinoma is the strongest argument support ing the existence of this clinical unit, which has never been explained in another way [5][6][7].…”
Section: Case Reportmentioning
confidence: 99%